2019
DOI: 10.1159/000499385
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Leptin Is Associated with Alterations in Thyroid-Stimulating Hormone Levels after Roux-en-Y Gastric Bypass Surgery in Obese Euthyroid Patients with Type 2 Diabetes

Abstract: Background: Leptin has been shown to stimulate the hypothalamus-pituitary-thyroid (HPT) axis in vivo and vitro. Its role in thyroid axis regulation after weight loss induced by bariatric surgery is still unknown. The aim of this study was to evaluate the influence of leptin on weight loss and thyroid function variation induced by Roux-en-Y gastric bypass (RYGB) surgery in euthyroid individuals with obesity and type 2 diabetes mellitus (T2DM). Methods: 65 Chinese individuals with obesity and T2DM who underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Leptin regulates appetite and food intake and stimulates the secretion of hypothalamic hormones, such as TRH. Yu et al demonstrated that TSH was significantly positively related with BMI, CRP, and leptin, reasoning that leptin might mediate change in thyroid function via cross talk between adipose tissue and hypothalamic pituitary thyroid axis [123]. To conclude, it is noteworthy that most studies revealed a beneficial effect of bariatric surgery on hypothyroid patients, considering thyroid function and a decrease of drug requirements.…”
Section: Bariatric Surgerymentioning
confidence: 99%
“…Leptin regulates appetite and food intake and stimulates the secretion of hypothalamic hormones, such as TRH. Yu et al demonstrated that TSH was significantly positively related with BMI, CRP, and leptin, reasoning that leptin might mediate change in thyroid function via cross talk between adipose tissue and hypothalamic pituitary thyroid axis [123]. To conclude, it is noteworthy that most studies revealed a beneficial effect of bariatric surgery on hypothyroid patients, considering thyroid function and a decrease of drug requirements.…”
Section: Bariatric Surgerymentioning
confidence: 99%
“…Mean free thyroxine levels decreased from 16.26 pmol/L to 14.59 pmol/L ( P < 0.01) and thyroid-stimulating hormone (TSH) levels decreased significantly (2.19 ± 1.09 mIU/L vs. 1.97 ± 1.12 mIU/L, P = 0.027) at 6 months after RYGB ( Liu et al, 2017a ). In other studies, thyroid hormones including free triiodothyronine, free thyroxine, and TSH declined in parallel at 12 months after RYGB and SG ( Yu et al, 2019 ; Zhu et al, 2019a ). However, weight loss after SG is accompanied by a significant decrease in serum TSH level, but no change in serum free thyroxine or free triiodothyronine levels ( Yang et al, 2017 ).…”
Section: Evaluation Of Metabolic Surgery Efficacy For Obesity and T2dmmentioning
confidence: 70%
“…However, weight loss after SG is accompanied by a significant decrease in serum TSH level, but no change in serum free thyroxine or free triiodothyronine levels ( Yang et al, 2017 ). Decreased TSH levels after weight loss induced by RYGB might be mediated by a decline in leptin ( Yu et al, 2019 ). However, patients after RYGB have a potential risk of thyroid nodule progression ( Zhang et al, 2017b ).…”
Section: Evaluation Of Metabolic Surgery Efficacy For Obesity and T2dmmentioning
confidence: 99%
“…It is believed to play a relevant role in the hypothalamic-pituitary-thyroid (HPT) axis by regulating the TRH gene expression. A positive correlation between the decrease in leptin levels after bariatric surgery and the reduction in TSH has been observed in euthyroid patients [19]. However, a retrospective study did not found a signi cant association between the decrease in plasma leptin level and the decrease in levothyroxine dose [8].…”
Section: Discussionmentioning
confidence: 99%